The Influence of We the Fest Event Satisfaction on the Decision to Visit Jakarta - Kurniawati, Rina; Tariska, Ade (Politeknik Pariwisata NHI Bandung, 2025)
This study examines the influence of visitor satisfaction on the decision to visit Jakarta, using an international music festival We the Fest (WTF) as a case study. WTF is an annual large-scale event that combines music performances, arts, fashion, and culinary experiences, organized by Ismaya Live in Jakarta. The research employed a quantitative method with purposive sampling involving 96 respondents from outside Jakarta who had attended WTF at least once. Data were analyzed using Pearson Product Moment correlation, coefficient of determination (R²), and t-test, utilizing SPSS v25. The results indicate a significant influence of event satisfaction on the decision to visit Jakarta, with a t_count value of 8.521 > t_table (1.986) and a significance value of 0.000 < 0.05. The coefficient of determination (R²) of 0.436 suggests that 43.6% of the variance in visiting decisions is influenced by satisfaction with WTF, while the remaining 56.4% is affected by other factors not examined in this study. These findings have important implications for event organizers and urban tourism managers, particularly in enhancing the quality of visitor experiences to encourage repeat visits and strengthen Jakarta's image as a tourism destination.